Combustion-derived nanocrystalline LiMn2O4 as a promising cathode material for lithium-ion batteries - Gao, X.; Sha, Y.; Lin, Q.; Cai, R.; Tade, Moses; Shao, Zongping (Elsevier, 2015)
In this study, nanocrystalline LiMn2O4 was synthesized by a simple combustion method and investigated for its utility as the positive electrode of a lithium-ion battery. X-Ray Diffraction characterization demonstrated that a basic crystallized spinel phase was already formed in the primary product from the direct combustion process, while pure phase LiMn2O4 was obtained after further calcination in air at relatively low temperature of 600 °C. Characterization by SEM and HR-TEM as well as BET analysis showed that the LiMn2O4 compound had a primary particle size of 40–80 nm and that those particles were partially sintered to form 0.2–0.8 μm aggregates with few mesopores. The exposed surface area of the aggregates was low and mainly formed by the outer surfaces of the constituent particles, which is beneficial to reducing the interfacial area between the liquid electrolyte and LiMn2O4, thereby effectively mediating the Mn dissolution problem. As a result, the as-prepared LiMn2O4 showed a favorable capacity of 114 mAh g−1 at a current rate of 0.2C and still retained a capacity of 84 mAh g−1 at 5C. After 100 continuous cycles at 0.1C, a capacity of 108 mAh g−1 was still maintained, compared to 120 mAh g−1 at the first cycle. The results demonstrated that combustion synthesis-derived LiMn2O4 is a promising cathode material for lithium ion batteries (LIBs).